STUDI FENOMENOLOGI GAYA HIDUP SEHAT AKTIF KONSUMEN HERBALIFE DALAM PERSPEKTIF TECHNOLOGY OF THE SELF MICHEL FOUCAULT - Athika Dwi Wiji Utami (Communications, 2022)
An active healthy lifestyle popularized by Herbalife Nutrition caters for everyone – men, women, and young, by combining active activity and regular exercise with healthy nutrition. In this study, a phenomenon of an active healthy lifestyle applied by Herbalife consumers will be described, and then this phenomenon is associated with Michel Foucault's technology of the self-perspective approach. In Foucault's perspective, the informants disciplined themselves to follow Herbalife's active healthy lifestyle patterns. They will be committed to this lifestyle even though at the same time they are not aware that they are being hegemoned on the discourse of healthy and ideal body construction.